Microsoft Windows Vista : quick reference guide to mastering all that is Vista - Magid, Larry; Silverman, Dwight (Berkeley, California : Peachpit Press, 2007)
A volume geared to learners of all kinds and levels, an introduction to Microsoft Vista provides a series of lessons, as well as hands-on exercises and subject related sections, that teach users how to navigate the operating system's new interface, organize and access files, take advantage of new multimedia and security features, utilize Windows Sidebar and Internet Explorer 7, and more.
Lesson 1. Meet Vista -- Lesson 2. Upgrade to Vista -- Lesson 3. Get to know Vista -- Lesson 4. Use other programs with Vista -- Lesson 5. Find it with Vista search -- Lesson 6. Make Vista safer and more secure -- Lesson 7. Backing up is (not) hard to do -- Lesson 8. Manage information using gadgets -- Lesson 9. Discover Internet Explorer 7 -- Lesson 10. Work with images -- Lesson 11. Consume and create media -- Lesson 12. Enhance your productivity -- Lesson 13. Go mobile -- Lesson 14. Vista on the network -- Lesson 15. Get into games -- Lesson 16. Troubleshoot Vista.
Includes index.
Keywords: OPERATING SYSTEMS (COMPUTERS)